2017
DOI: 10.5551/jat.34645
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Arterial Stiffness and Blood Pressure Drop During the Sit-to-stand Test in Patients with Diabetes Mellitus

Abstract: Aim: Patients with orthostatic hypotension (OH) have high arterial stiffness. Patients with diabetes mellitus (DM) often have cardiac autonomic neuropathy that leads to OH; however, whether OH is an indicator of arterial stiffness progression is unclear. We aimed to investigate whether the cardioankle vascular index (CAVI) varies between DM patients with and without OH using the sit-to-stand test (STST).Methods: One hundred and fifty-nine patients with DM underwent CAVI assessment and blood pressure (BP) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…Electrodes were placed on both wrists. Beat-to-beat HR was assessed on the ECG, and HRV indices and respiratory rate were measured using the “Kiritsu Meijin” (Crosswell Co., Inc., Yokohama, Japan) [ 33 ], which included a HR monitor LRR-03 (GMS, Tokyo, Japan). The majority of previous studies have used spectral techniques based on the Fast Fourier Transform (FFT).…”
Section: Methodsmentioning
confidence: 99%
“…Electrodes were placed on both wrists. Beat-to-beat HR was assessed on the ECG, and HRV indices and respiratory rate were measured using the “Kiritsu Meijin” (Crosswell Co., Inc., Yokohama, Japan) [ 33 ], which included a HR monitor LRR-03 (GMS, Tokyo, Japan). The majority of previous studies have used spectral techniques based on the Fast Fourier Transform (FFT).…”
Section: Methodsmentioning
confidence: 99%
“…Third, in principle, when measuring BP while standing, it is recommended to measure it at 1 and 3 min after standing [27]. However, a study on patients with diabetes reported that BP values immediately after standing are the most sensitive markers of arterial stiffness compared with BP values afterward [28]. In addition, since symptoms associated with OH, such as dizziness and falling, are often seen immediately after standing, BP measurements in the present study were taken both immediately and 1 min after standing.…”
Section: Discussionmentioning
confidence: 99%
“…Electrodes were placed on both wrists. Beat-to-beat HR was assessed on the electrocardiogram, and HRV indices and respiratory rate were measured using the software program Kiritsu Meijin (Crosswell Co., Inc., Yokohama, Japan) [40] and the HR monitor LRR-03 (GMS, Tokyo, Japan). The majority of previous studies have used spectral techniques based on the fast Fourier transform algorithm, which is insufficient to estimate the precise power spectral density from short time series data.…”
Section: Methodsmentioning
confidence: 99%